Chloroplot: An Online Program for the Versatile Plotting of Organelle Genomes - Zheng, Shuyu; Poczai, Peter; Hyvönen, Jaakko; Tang, Jing; Amiryousefi, Ali (Frontiers in Genetics, 2020)
Understanding the complexity of genomic structures and their unique architecture is linked with the power of visualization tools used to represent these features. Such tools should be able to provide a realistic and scalable version of genomic content. Here we present an online organelle plotting tool focused on chloroplasts, which was developed to visualize the exclusive structure of these genomes. The distinguished unique features of this program include its ability to represent the Single Short Copy (SSC) regions in reverse complement, which allows the depiction of the codon usage bias index for each gene, along with the possibility of the minor mismatches between Inverted Repeat (IR) regions, and user-specified plotting layers. The versatile color schemes and diverse functionalities of the program are specifically designed to reflect the accurate scalable representation of the plastid genomes. We introduce a Shiny app website for easy use of the program; a more advanced application of the tool is possible by further development and modification of the downloadable source codes provided online. The software and its libraries are completely coded in R, available at https://irscope.shinyapps.io/chloroplot/.